Predictors of suicidal ideation in Korean American older adults: analysis of the Memory and Aging Study of Koreans (MASK) - Na, Peter J. (Int J Geriatr Psychiatry, 2016)
OBJECTIVE: Our aim is to investigate the prevalence and predictors of suicidal ideation among Korean American older adults and assess the self-rated mental health of Korean American older adults with suicidal ideation with or without depressive syndrome. METHODS: The Memory and Aging Study of Koreans is a cross-sectional, epidemiologic study of a community-representative sample of Korean American older adults (N = 1116) residing in the Baltimore–Washington area. Participants were interviewed using the Korean version of the Patient Health Questionnaire (PHQ-9K). In addition, demographic information, self-rated mental health, and self-rated physical health status were obtained. RESULTS: In this study, 14.7% of Korean American older adults reported suicidal ideation. Predictors of suicidal ideation included living alone, major or minor depressive syndrome (diagnosed by the PHQ-9K), shorter duration of residency in the USA, and poorer self-rated mental health status. Of those who reported suicidal ideation, 64% did not have minor or major depressive syndrome. However, their self-rated mental health was as poor as that of those with major or minor depressive syndrome but without suicidal ideation. CONCLUSION: Suicidal ideation without depressive syndromes was common among Korean American older adults. For this group of elders with poor self-rated mental health, future studies should look to improving early detection of suicide risks and developing feasible suicide prevention interventions.